The Representation of Symbols in Wolfgang Borchert's Short Story Nachts Schlafen Die Ratten Noch - Putri, Calista; Surya, Rismauliya Melati; Syahyananda, Jovita; Rosyidah (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2025)
This article explores the representation of symbols in Wolfgang Borchert’s short story Nachts schlafen die Ratten noch, which reflects the social and psychological conditions of post-war German society. The story portrays trauma, grief, and subtle hope through simple yet powerful symbols. Symbols such as urban ruins, rats, and characters are analyzed to uncover deeper meanings related to themes of trauma, humanity, and hope. This study adopts a qualitative approach, using literature review as the primary method. Stuart Hall’s theory of representation and Charles Sanders Peirce’s theory of signs provide the theoretical foundation to examine how symbols construct meaning. The analysis reveals that the symbols in this short story not only reflect post-war realities but also convey universal humanistic messages. Through this approach, the article highlights the essential role of symbolism in literature as a medium for expressing emotions, collective experiences, and social meanings that cannot always be conveyed explicitly.